Pengaruh Putaran Spindel dan Cairan Pendingin terhadap Kekasaran Permukaan Baja AISI 4140 pada Proses Pembubutan - Angga Hari Setyawan; Iswanto Iswanto (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2019)
The purpose of this paper discusses how the effect of different spindle spin speeds on surface roughness, how the effect of different coolant fluid on surface roughness and is there an interaction between rotation speed of spindle and coolant to surface roughness in conventional lathe process. In this study the variable varied is the spin speed of the spindle that is is 630 rpm, 920 rpm, and 1250 rpm and the variation of coolant used is coolant, used cooking oil, and used SAE 40 oil. Then the surface roughness test was done. From the results of surface roughness test previously done the lathe process with variations of rotation speed of spindle and coolant, it can be concluded that: the highest surface roughness value was obtained during the turning process using used cooking oil coolant and spindle rotation used at 920 rpm. While the lowest value of surface roughness of the workpiece is obtained when using used SAE 40 oil coolant using a spindle rotation of 1250 rpm.